2011
DOI: 10.1021/jp111890d
|View full text |Cite
|
Sign up to set email alerts
|

Stable Magnetic Chemical Locomotive with Pd Nanoparticle Incorporated Ferromagnetic Oxide

Abstract: In this article, we present results on the development of a new magnetic chemical locomotive made of ferromagnetic cobalt ferrite (CoFe2O4), doped with Pd nanoparticles (NPs). The composite particles were found to be chemically stable in realizing magnetic chemical propulsion. Further, these particles strongly catalyzed the decomposition of hydrogen peroxide (H2O2) solution even when the strength of the solution was as low as 0.3%, making it efficient in inducing autonomous chemical locomotion. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…22 During the reaction, the hydroxyl radical ˙OH is the key to the formation of O 2 gas bubbles. 23 Based on the reaction mechanism, when the chemical quencher (DMSO in this case) is present, the rate of O 2 gas generation is given by: 23 where [S] stands for the active metal surface, k D , k 1S and k 2S represent the constants in the reaction processes and [DMSO] and [H 2 O 2 ] are the concentrations of DMSO and hydrogen peroxide in the solution, respectively. From the above equation, the generation of oxygen gas depends on three factors: the concentration of hydrogen peroxide, the amount of DMSO (or other molecules that are able to quench the radical reaction) as well as the active surface area of the catalyst metal, Pt.…”
Section: Resultsmentioning
confidence: 99%
“…22 During the reaction, the hydroxyl radical ˙OH is the key to the formation of O 2 gas bubbles. 23 Based on the reaction mechanism, when the chemical quencher (DMSO in this case) is present, the rate of O 2 gas generation is given by: 23 where [S] stands for the active metal surface, k D , k 1S and k 2S represent the constants in the reaction processes and [DMSO] and [H 2 O 2 ] are the concentrations of DMSO and hydrogen peroxide in the solution, respectively. From the above equation, the generation of oxygen gas depends on three factors: the concentration of hydrogen peroxide, the amount of DMSO (or other molecules that are able to quench the radical reaction) as well as the active surface area of the catalyst metal, Pt.…”
Section: Resultsmentioning
confidence: 99%
“…Similar experiments were also performed with cobalt ferrite microparticles, which were doped with palladium. 44 In a solution of hydrogen peroxide, propulsion of the particles was determined by oxygen formation on the particle surface. The authors demonstrated that small magnetic elds could be used to align and hence steer the ferromagnetic particles.…”
Section: Inhomogeneous Magnetic Elds and Ferromagnetsmentioning
confidence: 99%
“…In addition, it is also possible to collect and entrap the particles with a sufficiently strong magnetic field. It might be noted that magnetic control of the trajectory of particles has for instance also been reported for the case of 150 μm sized Pd‐CoFe 2 O 4 particles that decompose H 2 O 2 and move on the liquid surface or hollow microparticles made of MnFe 2 O 4 …”
Section: Resultsmentioning
confidence: 78%